Student Midwives' Duty Hours: Risks, Standards, and Recommendations. (10th March 2014) - Lawrence, Rachel; Kantrowitz‐Gordon, Ira; Landis, Andrea
<x xml:space="preserve">Abstract</x> Introduction A growing body of literature has emerged describing the risks of extended‐duty shifts and sleep deprivation. Worldwide, midwifery organizations have not adopted standards for practitioner or student duty shifts. This project reviews the literature related to extended‐duty shifts in an effort to develop evidence‐based recommendations for student nurse‐midwives/student midwives (SNMs/SMs). Methods A comprehensive literature search was conducted through electronic databases, major journals, and reference lists published in English since January 2001. Primary research studies evaluating sleep deprivation and shift duration were included. Studies that did not include the target population (shift workers) and those that formed conclusions related to extended‐duty shifts greater than 30 hours were excluded. In addition, an extensive worldwide review of duty‐hour recommendations from more than 300 health care organizations was conducted. Results A total of 40 studies met the inclusion criteria. Extended‐duty shifts (those greater than 12 hours) increased the risk for cognitive and physical functional errors, safety concerns, and decreased quality of life from sleep deprivation. Cognitive function errors included attention lapses, visual tracking errors, decreased mentation and immediate recall, and decreased learning capacity. Physical errors included decreased motor skills and slowed reaction times in clinical simulations. These deficits led to an increased risk of motor vehicle accidents, needle sticks, and performance equivalent to unsafe blood alcohol concentrations. An overall decrease in quality of life and job satisfaction was linked to extended‐duty shifts. Seven organizations for medical residents or advanced practice nurses have developed policy statements on duty shifts, with extended‐duty shift limitations between 12 and 24 hours. Discussion The risks associated with extended‐duty shifts may inhibit the development of SNMs/SMs into competent practitioners and place patients at risk. It is recommended that midwifery education programs adopt evidence‐based limitations for the duty shifts of SNMs/SMs.